Applied cognitive task analysis methodology: Fundamental cognitive skills surgical nurses require to manage patient deterioration. - Marshall, Dianne; Finlayson, Mary (Nursing Praxis in Aotearoa New Zealand, 2022)
This study's aims were twofold: firstly, to identify the cognitive skills required of surgical nurses to rescue the deteriorating patient; and secondly, to elicit insight into the potential errors in decisionmaking inexperienced nurses commonly make in the same situation. An exploratory qualitative design used applied cognitive task analysis. A series of three in-depth interviews with six experienced surgical nurses were employed to collect the data. Applied cognitive task analysis interviews are sequential to identify different aspects of expert knowledge: the task diagram interview; the knowledge audit interview; and the simulation interview. Five difficult cognitive demands were identified when a patient is deteriorating: early recognition of physiological deterioration; confirming physiological deterioration; initiating rescue; securing medical assistance; and rescuing the patient. Nurses require the following cognitive skills to respond effectively to these cognitive demands: decision-making; leadership and management; patient advocacy; situation awareness; and planning. Educators should be aware of these cognitive demands and the specific cognitive skills required to manage patient deterioration and design initiatives to help accelerate nurses' cognitive expertise and consequently reduce errors. The study also highlights the importance of adequate shift coverage with highly skilled nursing staff.